PENGARUH PENGETAHUAN, SIKAP KEUANGAN DAN PERSEPSI MANFAAT TERHADAP KEPUTUSAN PENGGUNAAN E-WALLET SEBAGAI TRANSAKSI PEMBAYARAN DIGITAL (STUDI PADA MAHASISWA UIN DATOKARAMA PALU) - Hidayah, Amalia Nurul; Ubay, Ubay; Badjarad, Rizqa Sabrina (Yayasan Nuraini Ibrahim Mandiri, 2025)
This study aims to analyze the influence of knowledge, financial attitudes, and perceived benefits on the decision to use e-wallets as digital payment transactions among students at UIN Datokarama Palu. This study uses associative research with a quantitative approach. The study utilizes primary data obtained through a questionnaire. The population size in this study is 6,734 individuals, with a sample size of 100 students from UIN Datokarama Palu. Data analysis was conducted using SPSS version 30. The results indicate that, partially (t-test), knowledge, financial attitudes, and perceived benefits have a positive and significant influence on the decision to use e-wallets. Additionally, simultaneously (F-test), the three variables also have a positive and significant influence on the decision to use e-wallets, with a coefficient of determination (R²) of 0.697. This means that 69.7% of the decision to use e-wallets is influenced by the three variables, while the remainder is influenced by factors outside the scope of this study. These findings indicate that the higher the knowledge, financial attitude, and perceived benefits, the higher the decision to adopt e-wallets among students.